Ejendomsordbogen fransk/dansk: ny integreret e-ordbog - Leroyer, Patrick; Kruse, Liselotte (Nordiske Studier i Leksikografi, 2012)
This article outlines the theoretical and practical considerations that have guided the planning and compiling of the French/Danish Real Estate e-Dictionary, a new online specialized dictionary which is now available and fully operational at Ordbogen.com. The genuine purpose of the dictionary is to assist its intended Danish users in solving foreseen, typical communication and knowledge-related problems in various real estate situations such as searching for and buying, selling, or owning a property in France. The dictionary is innovative in a number of ways as it is deliberately polyfunctional, but has been specifically designed to match the various needs of its intended user groups (experts and semi-experts with various degrees of proficiency in French) thanks to an adaptive data access and presentation. It also features a pragmatic user interface allowing consultation according to the situation of the users in relation to their practical real estate situation: searching, buying, owning or selling a property.